Assessing Choroidal Thickness in Central Serous Chorioretinopathy Using Swept-Source Optical Coherence Tomography - Arab, Muntasser Mohammed; Alshalchi, Abeer AbdulRazzaq Hadi; Abbas, Mohammad Asaad (South Asian Journal of Social Sciences and Humanities, 2024)
Background: Central serous chorioretinopathy (CSC) is a retinal condition marked by the build-up of fluid beneath the retina., disrupting vision. This study evaluates the use of Swept Source Optical Coherence Tomography (SS-OCT) to measure choroidal thickness, which could help in understanding and managing CSC. Study objectives: To determine the differences in choroidal thickness between affected eyes by active CSC and the unaffected contralateral eyes, and a control group. Methods: A case-control study involving 23 CSC patients and 37 healthy controls. Choroidal thickness was measured using SS-OCT. Statistical analysis was used to compare measurements across the groups. Results: The study found significantly increased choroidal thickness in eyes of patients with CSC compared to both contralateral unaffected and control eyes, suggesting the utility of SS OCT in identifying and managing CSC. Conclusion: SS-OCT is an effective tool for distinguishing CSC from other conditions and monitoring its progression. Increased choroidal thickness is a notable feature of CSC-affected eyes, highlighting the importance of choroidal evaluation in CSC diagnosis and treatment.